IMPROVED METHOD FOR THE SYNTHESIS AND ISOLATION OF SCHIFF BASE FUNCTIONALIZED N-HETEROCYCLIC CARBENE LIGAND PRECURSORS - ABUBAKAR, SAMAILA; AHMED PANTAMI, HAMZA; UMAR BARAMBU, AISHATU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
We reported herein, the synthesis, and characterization of a series of Schiff base functionalized N-heterocyclic carbene ionic salts, the synthesis involved the heating of the Schiff base and the carbene moieties at 60 ⁰ C for 30 minutes. It does not involves the use of a solvent and all products were isolated in excellent yields between 95 and 98%. The synthesized compounds which are precursors to Nhetero cyclic carbene ligands were characterized using spectroscopy.